Name It, Claim It, Grab It: African Neo-Pentecostal Faith and Hope Gospel - White, Peter; Aikins, Rachel P. (Journal of Pentecostal Theology, 2021)
Pentecostalism being a global phenomenon has become an interesting subject inGlobal Christianity and academic discourses. Numerous scholars have researchedand published articles on it from various perspectives. This article discusses AfricanPentecostalism by bringing fresh discussion on the existing literature on ‘prosperitygospel’. The article argues that Pentecostal preachers are not prosperity gospelpreachers but rather preachers of a faith and hope gospel. The article conceptualises thefaith and hope gospel from a Biblical perspective as well as the theological perspectiveof the adherents and practitioners of Pentecostal theology. Although the articleacknowledges the extremist approach of some of the adherents and practitionersin their interpretation of scriptures and sometimes the abuses, the article arguesthat the dynamic and contextual nature of theology should be considered while theabuses are also objectively condemned. The article discusses debates on Pentecostalhermeneutics as well as the characteristics of the three perspectives of the faith andhope gospel by using the terms ‘name it, claim it, grab it’.
free